(untitled) (Mantichora. Italian Journal of Performance Studies, 2024)
It is noteworthy to examine the ricochet game, an exercise in throwing stones accurately, that was largely practised in Greco-Roman Antiquity among others shooting games. Conceptually, this ludic performance contains elements of risk, skill, reaction and trajectory. The universal water-ricochet game is known in Greek as epostrakismos and today in English as “ducks and drakes”. Apart of Ancient (Pollux of Naukratis) and Byzantine lexicographers (Eustathius of Thessalonica, Etymologicum Magnum), 2nd-century Latin Apologist Minucius Felix provided the most accurate and liveliest description of this game in his dialogue Octavius, where he portrays children performing the ricochet game on the beach of Ostia. Modern Greek and Italian folklore also knows ricochet games and literary echoes to ricochet-performance can also be found in Manzoni’s novel The Betrothed as well as in 20th-century poem written by Fernando Bandini.